Il costo medio per tipologia di prestazione nei centri trasfusionali - Martina, Silvia; Cornago, Dante; Garattini, Livio; Castelnuovo, Emanuela (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
In Italy the collection, validation and separation of blood and its derivatives for transfusional interventions are carried out by some 380 transfusional centers (TCs), mainly located within greater health care structures. The aim of the CORSA (Costi Raccolta Sangue) study was to furnish an estimate of the mean cost of the main transfusional services on a sample of the Italian TCs. Of the centers contacted, only 13,3% were able to deliver the unit costs necessary to perform the full-cost, fully-allocated analysis conducted. Of the three services examined (apheresis of plasma and platelets, whole blood collection), the selective collection of thrombocytes resulted the most expensive, as opposed to whole blood collection. The mean cost of a erythrocyte, plasma and platelet unit resulted of 17,7, 21,6 and 89,8 •, respectively, although the variation among centers was substantial. To main conclusions can be drawn by the CORSA study. First, the very low percentage of TCs able to provide the necessary data for a complete economical analysis highlights an important delay in the modernizing process of health care management, started in 1992 with the aim to ameliorate resource allocation. Second, the study was not able to establish a relationship between production volume and production cost, indicating the absence of scale economy features in transfusional processes.